Metabolic view involving depression and heart failure: a reflective analysis (Research, Society and Development, 2020)
The present work can be reflexively analyzed based on the literature on metabolic association involving depression in patients with heart failure. The method described as a descriptive study, the type of reflective analysis, with the discussion of the literature on: metabolism, depression and heart failure. As a result, studies show that heart failure influences neurobiological systems, within genetic limits, leading to behavioral manifestations of depression. These metabolic cascades in heart failure contribute to the pathophysiology of depression. The role of depression and the imbalance of the health-disease process are related to multifactorial causes. However, knowing what happens between depression, its oldest form when associated with heart failure and the development of psychic behavior, especially depression, is essential to guide mental health care practices, both in the interventionist and in the preventive scope. Further studies in the cardiopsychiatric metabolic area are necessary.